2010
DOI: 10.21608/mjae.2010.104808
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Management of Surface Drip Irrigation Systems

Abstract: Recently maintenance operation is considered one of the main axes of engineering management of pressurized irrigation systems. There for the aim of this research work was to select the most suitable maintenance programs to improve drip irrigation systems laterals performance, and decrease the damages caused by emitter clogging as a result of bad maintenance applications. The physical maintenance programs included lateral end flushing with two different operation times"5, 10 minutes at the end of each irrigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…The common type of pipes system is perforated pipes technique, which is a simplified type of gated pipes. El-Berry et al (2006) reported that using developed surface irrigation system saved applied irrigation water by about 30.54% to 37.37% compared with traditional irrigation system. Abd El-Rahman (1985) concluded that water efficiencies increased as flow rate and soil slope increased.…”
Section: Introductionmentioning
confidence: 99%
“…The common type of pipes system is perforated pipes technique, which is a simplified type of gated pipes. El-Berry et al (2006) reported that using developed surface irrigation system saved applied irrigation water by about 30.54% to 37.37% compared with traditional irrigation system. Abd El-Rahman (1985) concluded that water efficiencies increased as flow rate and soil slope increased.…”
Section: Introductionmentioning
confidence: 99%